Pengaruh Pelatihan dan Komitmen Kerja Terhadap Kinerja Pegawai dengan Disiplin Kerja Sebagai Variabel Intervening pada Dinas Perhubungan Kota Solok - Suzana, Harry; Yulasmi, Yulasmi; Veri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the effect of training and work commitment on employee performance with work discipline as an intervening variable at the Solok City Transportation Office. This study uses a quantitative approach. The data analysis techniques used were multiple linear regression analysis and path analysis, by distributing a questionnaire of 87 respondents to employees of the Solok City Transportation Office. The results of the study showed that there was a positive and significant effect of training on work discipline at the Solok City Transportation Agency. There was a positive and significant effect of work commitment on work discipline at the Solok City Transportation Agency. There was a positive and significant effect of training on employee performance at the Solok City Transportation Agency. There was a positive and significant effect of work commitment on employee performance at the Solok City Transportation Agency. There was a positive and significant effect of work discipline on employee performance at the Solok City Transportation Agency. Work discipline was able to mediate the effect of training on employee performance at the Solok City Transportation Agency. Work discipline was able to mediate the effect of work commitment on employee performance at the Solok City Transportation Agency